2014
DOI: 10.1007/s40092-014-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Markov modeling and reliability analysis of urea synthesis system of a fertilizer plant

Abstract: This paper deals with the Markov modeling and reliability analysis of urea synthesis system of a fertilizer plant. This system was modeled using Markov birth-death process with the assumption that the failure and repair rates of each subsystem follow exponential distribution. The first-order Chapman-Kolmogorov differential equations are developed with the use of mnemonic rule and these equations are solved with Runga-Kutta fourth-order method. The long-run availability, reliability and mean time between failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A.K. Aggarwal et al [4] explained about the performance modelling and availability analysis of the Urea Synthesis System in fertilizer production plant. From the research and analysis studies they are produced to the suitable maintenance techniques for increase the performance of the subsystem availability in the fertilizer production plant by using the Transition Diagram of the Urea Synthesis system, Markov model, First order Chapman -Kolmogorov differential equations and these equations are solved by the Range Kutta fourth order method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A.K. Aggarwal et al [4] explained about the performance modelling and availability analysis of the Urea Synthesis System in fertilizer production plant. From the research and analysis studies they are produced to the suitable maintenance techniques for increase the performance of the subsystem availability in the fertilizer production plant by using the Transition Diagram of the Urea Synthesis system, Markov model, First order Chapman -Kolmogorov differential equations and these equations are solved by the Range Kutta fourth order method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Garg et al (2010) proposed a new technique in the plywood industry to find the reliability model of a block-board manufacturing system. Aggarwal et al (2015) reported a mathematical model of the fertilizer plant of the urea synthesis system to find the mean time between failure and reliability analysis. Mangey and Manglik (2016) considered numerous aspects of failure and the reliability parameters of the dynamic repairable manufacturing system had been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar (2014) performed availability analysis of a thermal power plant boiler air circulation system using the Markov approach. Savsar (2015) proposed the availability analysis of a power plant by computer simulation and, further, Aggarwal et al (2015) developed the mathematical model for reliability analysis of a urea synthesis system of a fertilizer plant.…”
Section: Introductionmentioning
confidence: 99%